HINDU THEO-LINGUISTICS: SANSKRIT AS THE LANGUAGE OF HINDU THEOLOGY IN LONTAR BHUWANA SANGKSEPA - Putu Eka Sura Adnyana; I Nyoman Suarka; Relin D.E; Ni Nyoman Suryani (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Sanskrit has its prestige for the narrators, thus encouraging the narrators to use Sanskrit terminology and Sanskrit vocabulary in the process of composing Kawi literature. One of the types of literature referred to and contains philosophical, religious, and life values is the Tutur text. Bhuwana Sangksepa is a speech text that uses two languages, namely Sanskrit and Old Javanese, in the content of the text. This paper uses the theory of Theo-linguistics which is an interdisciplinary theory, that etymologically comes from the words theology and linguistics. In addition, to support data acquisition in data collection, it is also combined with interview techniques. Interview techniques are often referred to as interviews. The method of analyzing language research data is the agih method (distributional method) and the translational pairing method. The analyzed data will then be presented using formal and informal methods. Lontar Bhuana Sangkṣepa is one of the important lontar that contains the teachings of Hinduism (Siwatattwa). The text of Lontar Bhuana Sangkṣepa contains a dialog between Bhaṭāra Śiwa and Bhaṭāri Uma accompanied by Bhaṭāra Kumara. Lontar Bhuana Sangkṣepa consists of 128 śloka of Sanskrit with Old Javanese. Lontar Bhuwana Sangkṣepa can be understood as one of the oldest lontars, but after lontar Bhuwana Kośa and Jñana Siddhanta. The texts included in this category are most likely the oldest because as a benchmark for the use of Sanskrit śloka contained in the text, they reflect the situation at a time when Sanskrit texts were still circulating in the archipelago and the language was still actively used and well understood by scholars. The implementation of Sanskrit in śloka through Old Javanese/Kawi language commentary that contains Hindu theological teachings, namely: Bhaṭāra Śiwa, Iṣṭa Dewatā, Sṛṣti Bhuwana Agung, Śūnya, Swara-Wyañjana, Smarana, Nirbāṇa/Nirvāṇa, and Pralaya.